Elimination of TRIMS : the experience of selected developing countries (UN New YorkUS, 2007)
Sheds light on the implications of the elimination of Trade-Related Investment Measures (TRIMS). Considers the experience of four countries that notified TRIMs in 1995 viz. Argentina, Mexico, Pakistan and the Philippines. Covers two countries that, when the project was started, were seeking to accede to WTO viz. Ethiopia and Vietnam. Includes these two countries in order to examine the likely impact of WTO accession on their use of selected TRIMs.
Keywords: INVESTMENT